Cytomegalovirus Infection in Pediatric Renal Transplantation and the Impact of Chemoprophylaxis With (Val-)Ganciclovir. Issue 4 (April 2016) - Höcker, Britta; Zencke, Sebastian; Krupka, Kai; Fichtner, Alexander; Pape, Lars; Dello Strologo, Luca; Guzzo, Isabella; Topaloglu, Rezan; Kranz, Birgitta; König, Jens; Bald, Martin; Webb, Nicholas J. A.; et al.
Abstract : Background: Cytomegalovirus (CMV) replication and disease, with its associated morbidity and poor transplant outcome, represents a serious threat to transplant recipients. The pediatric kidney transplant population is at a particularly increased risk of CMV infection. Methods: We therefore analyzed CMV epidemiology in a large cohort of pediatric renal transplant recipients (n = 242) and assessed the impact of antiviral chemoprophylaxis with valganciclovir (VGCV) or ganciclovir (GCV) on CMV replication and morbidity. Results: While antiviral chemoprophylaxis with VGCV or GCV in patients with a high (D+/R−) or intermediate (D+/R+) CMV risk (n = 82) compared to preemptive therapy (n = 47) had no significant effect on the incidence of CMV syndrome or tissue-invasive disease, chemoprophylaxis was associated with a better preservation of transplant function at 3 years posttransplant (loss of estimated glomerular filtration rate in the chemoprophylaxis cohort, 16.0 ± 3.4 vs . 30.1 ± 4.7 mL/min per 1.73 m 2 in the preemptive therapy cohort, P < 0.05).CMV replication was associated with a more pronounced decline of graft function (difference in estimated glomerular filtration rate of 9.6 mL/min per 1.73 m 2 at 3 years) compared to patients without CMV replication. However, patients undergoing VGCV or GCV chemoprophylaxis had more leukocytopenia. Conclusion: Antiviral chemoprophylaxis with VGCV or GCV in recipients with a high or moderate CMV risk is associated with a better preservation of transplant function. Hence, the prevention of CMV replication in this patient population has the potential to improve transplant outcome. Abstract : In pediatric kidney transplant recipients at high and moderate CMV infection risk, chemoprophylaxis and preemptive therapy compared with regard to prevention of CMV-syndrome and tissue-invasive CMV disease but chemoprophylaxis was associated with a 3-year better graft function preservation and leukocytopenia. Supplemental digital content is available in the text.